Being a human being and how art can help. Issue 1 (1st March 2016) - Wienk, Janeke
Based on the author's experience, this Interlude explores the different ways in which art can help reflect on artistic, pedagogical and existential key questions that are relevant to both personal and professional contexts. The lived experience of how being in touch with art helps one to be in touch with one's own humanity can be a powerful starting point to art education. This Interlude aims to bridge the gap between an instrumentalized arts curriculum and the natural ability of art to connect us to the very base of human existence.